1971 EDN Caravan Exhibit - Armstrong & Hess (1971)
This series of photographs document Beckman's EDN Caravan exhibit, including a display for The 3-cent Resistor and apparent back-stage shots.
Keywords: Trade shows; Beckman Instruments, Inc.